Misleading or Informing? Examining the Effects of Labeling Design on Consumers’ Perception of Gluten-Free Products and Wheat Safety - Kimberly Cantrell; Nan Li; Courtney Meyers; Cindy Akers (Journal of Applied Communications, 2020)
As food products marketed as “gluten-free” become increasingly popular, many consumers start to exclude sources of gluten (e.g., wheat, barley, and rye) from their diets for both medical and non-medical purposes. The grain industry is facing a growing challenge to (re)boost consumers’ confidence in the healthiness and safety of its commodities. Using 561 participants recruited from the Amazon Mechanical Turk workers’ panel, this study implemented a 2 (pretzels vs. potato chips) * 2 (positive- vs. negative- frame) * 2 (wheat image vs. no wheat image) experiment to examine the effects of gluten-free labels on consumers’ perceived healthiness and safety of wheat, perceived benefits of labeled products, and their evaluation of the shown labels. Results showed that consumers evaluate the gluten-free labels most positively when they appear on products that could have contained gluten. For products that are naturally gluten-free, adding a gluten-free label only decreased consumers’ confidence in such labels. The presence of gluten-free labels increased consumers’ perceived benefits of the labeled products when they do not contain any misleading information (e.g., image of a wheat head). However, some gluten-free labels could have negative impacts on consumers’ perceptions of the healthiness and safety of wheat. Overall, food producers and marketers might have undervalued consumers’ literacy and overestimated their susceptibility to marketing strategies. We discussed the implications for food marketers, regulators, and communicators.
Keywords: gluten-free; wheat; labeling; framing; marketing